The Life Writings of Mary Baker McQuesten (1849--1934): Victorian Matriarch of Whitehern - Anderson, Johanna Mary (My University, 2000)
My aim in this research is the recovery and presentation of Mary Baker McQuesten's life writings which will add to the growing body of women's literary, cultural and political history in Hamilton, in Ontario and in Canada. Mary Baker McQuesten (1849-1934) was an exceptional and enlightened women of the Victorian and Edwardian age in Canada, yet she is little known. Her writings reveal the political strength and matriarchal power that were possible for women in Ontario during the extended Victorian era. Although Mary never wrote for publication, she was a prolific and uninhibited letter writer; more than five hundred of her letters are extant, mostly those written to her children. She was also a forceful and impassioned speaker and wrote and delivered many Presbyterian missionary society addresses. Mary's letters record the development of her matriarchal power after she suddenly became a widowed single-parent of six young children, and was forced to raise and educate them in a state of genteel poverty. Her writings give details of the family's financial problems and health concerns, such as inherited mental disease and tuberculosis. I have included extensive annotations to the letters to provide background material for the family's social scene, education, literature, politics, religion and social reform. Mary was a dynamic and determined matriarch in both the domestic sphere and in her public leadership, and she was a keen observer and an outspoken critic of her times. The theoretical section of the thesis offers an approach to the literary aspects of the McQuesten life writings through a review of critical and cultural theory, and provides the precedents that establish personal letter writing and auto\biography within the genre of life writing. The theoretical section also shows how the McQuesten writings are important to cultural and interdisciplinary studies in the Humanities and Social Sciences. The writings are a rich repository of Canadian Victorian ideas and ideals, and they are important cultural artifacts that provide insights into the Victorian family and society during a period of great change in Canada.
Keywords: English Language and Literature; English Language and Literature